Contribution of Uganda Women Entrepreneurship Program (UWEP) in Enhancing the Socio-Economic Welfare of Women in Ryakarimira Town Council Kabale District. - Kabonire, Racheal (Kabale University, 2025)
The purpose of this study was to find out “the contribution of Uganda women entrepreneurship program (UWEP) in enhancing the socio-economic welfare of women in Ryakarimira town council Kabale District”, and was guided by three objectives: to establish “the contribution of Uganda women entrepreneurship program (UWEP) in enhancing the socio-economic welfare of women in Ryakarimira town council Kabale District”, ii. to identify the challenges facing “the contribution of Uganda women entrepreneurship program (UWEP) in enhancing the socio-economic welfare of women in Ryakarimira town council Kabale District?”, iii. to establish the possible measures to the challenges facing women empowerment initiatives in the process of community development and welfare in Ryakarimira town council, Kabale District.